Arthroscopic reduction with non-fixation for Broberg & Morrey type II radial head fracture with mechanical rotation block: a propensity score-matched case-control study - Wang, Yanmao; Yu, Shiyang; Ding, Jian; Lu, Shengdi (Frontiers in Surgery, 2025)
AimsTo evaluate arthroscopic reduction without fixation (ARnF) for Broberg & Morrey Type II radial head fractures presenting with a mechanical block to forearm rotation.MethodsWe reviewed 11 patients with Broberg & Morrey Type II radial head fractures and a mechanical rotation block treated with ARnF. Clinical outcomes included elbow range of motion (ROM), the American Shoulder and Elbow Surgeons (ASES) score, and the Disabilities of the Arm, Shoulder and Hand (DASH) score. Outcomes were compared with those of patients who underwent arthroscopic reduction and internal fixation (ARIF) using cannulated screws at 6 weeks, 12 weeks, and 1 year postoperatively.ResultsEleven patients were included (7 male; mean age 33.6 years). All showed significant postoperative improvement. At each follow-up, mean ROM and both functional scores (ASES and DASH) in the ARnF group were comparable to those in the ARIF cohort.Conclusionor Broberg & Morrey Type II radial head fractures with a mechanical rotation block, ARnF achieved outcomes comparable to ARIF while avoiding implant costs and implant-related risks.Clinical Trial Registration: https://www.chictr.org.cn/, identifier (ChiCTR2000035958).Level of Evidence: LEVEL III; Treatment study; Case control study.